2020
DOI: 10.1007/s00417-020-04623-w
|View full text |Cite
|
Sign up to set email alerts
|

Response of neovascular central serous chorioretinopathy to an extended upload of anti-VEGF agents

Abstract: Purpose To determine the anatomical and functional outcomes of an extended 6-month intravitreal anti-vascular endothelial growth factor (anti-VEGF) upload in choroidal neovascularization (CNV) secondary to chronic central serous chorioretinopathy (CSCR). Methods A retrospective database analysis was performed applying the following inclusion criteria: (1) diagnosis of CSCR, (2) diagnosis of secondary CNV, and (3) treatment of at least six consecutive injections of anti-VEGF. Outcome measures included the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
(45 reference statements)
2
19
0
3
Order By: Relevance
“…Our results demonstrated that in the nCSC group, only the level of VEGF increased; other proinflammatory cytokines remained unchanged, which supports the current view that the mechanism of neovascularization in pachychoroid disease differs greatly from that in AMD (23). The results also provide a theoretical basis for the treatment outcome reported by another study in which all patients with nCSC exhibited reduced pigment epithelial detachment thickness after 6 months of intravitreal anti-VEGF injection treatment (18). In the nAMD group, the levels of the inflammatory cytokines IL-10 and IP-10 both increased.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results demonstrated that in the nCSC group, only the level of VEGF increased; other proinflammatory cytokines remained unchanged, which supports the current view that the mechanism of neovascularization in pachychoroid disease differs greatly from that in AMD (23). The results also provide a theoretical basis for the treatment outcome reported by another study in which all patients with nCSC exhibited reduced pigment epithelial detachment thickness after 6 months of intravitreal anti-VEGF injection treatment (18). In the nAMD group, the levels of the inflammatory cytokines IL-10 and IP-10 both increased.…”
Section: Discussionsupporting
confidence: 89%
“…Choroidal vessel hyperpermeability and congestion were suggested to be the cause of CSC (17), which is a disease in the pachychoroid spectrum. Secondary CNV in CSC is also called pachychoroid neovasculopathy (18), which may also be affected by the dysregulation and hyperpermeability of the choroidal vessels (19). To our knowledge, although previous studies have shown that the VEGF level in CSC eyes without neovascularization was similar to those in normal human eyes (20,21), no research has investigated the VEGF level in the AH of patients with nCSC.…”
Section: Discussionmentioning
confidence: 98%
“…Anti-VEGF treatment for chronic CSC with CNV is well-established [26]. Schworm et al [27] reported that extended (6-month) anti-VEGF therapy yielded CMT reduction and improved visual outcome in chronic CSC with CNV. Similarily, Matsumoto et al [28] reported that anti-VEGF therapy improved BCVA and CMT in pachychoroid neovasculopathy over a 2-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Although these treatments have notable benefits, they also have limitations and do not guarantee a complete resolution of SRF. In addition, antivascular endothelial growth factor therapy is usually not effective, except in patients with neovascular CSC [ 30 , 31 ]. Currently, there is no gold standard method used to manage CSC.…”
Section: Discussionmentioning
confidence: 99%